2009
DOI: 10.1002/qua.22296
|View full text |Cite
|
Sign up to set email alerts
|

An atomic charge study of highly ionic diatomic molecular systems

Abstract: Four atomic charge formalisms are compared using highly ionic diatomic molecules, such as LiF, NaF, KF, LiCl, NaCl, KCl, BF, AlF, GaF, BeO, and MgO. All calculations were done at the QCISD/6-311G(2df) level. The only formalism consistent with the characteristics of all these systems is Quantum theory of atoms in molecules (QTAIM). Absolute Mulliken charge values are small. ChelpG charges are not reliable for systems in which the atoms are largely anisotropic. Generalized atomic polar tensor values are contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Figure shows that Mulliken charges also compare well with the results of eq . Our results from eq are also in good agreement with literature values [Table S3 (SI)] from other quantum chemistry approaches.…”
supporting
confidence: 90%
“…Figure shows that Mulliken charges also compare well with the results of eq . Our results from eq are also in good agreement with literature values [Table S3 (SI)] from other quantum chemistry approaches.…”
supporting
confidence: 90%
“…8 Some other studies of various chemical properties of BeO have also been reported; for example the valence band gap of BeO has been studied by Soulé de Bas et al, 9 the valence states of BeO have been study by Sorensen et al, 10 and the low-lying states of BeO have been studied by Irisawa et al 11 The partial atomic charges and dipole moment of LiF, KF, BeO, and MgO have been studied by Nakazato et al 12 In the present paper, we will study the BDE, IP, EA, EE, IE, and dipole moments for fourteen main-group diatomic molecules and one triatomic molecule (KOH).…”
Section: Introductionmentioning
confidence: 97%
“…In this context, several charge formalisms, based on arbitrary ways to divide the molecular electronic charge among the constituent atoms, have been analyzed for diverse purposes. [1][2][3][4][5][6][7][8][9][10][11] Recently, we carried out a study comparing the use of Mulliken, 12,13 Natural Population Analysis (NPA) 14,15 and Quantum Theory of Atoms In Molecules (QTAIM) [16][17][18] models in obtaining intramolecular charge uxes during bond stretchings in diatomic and linear triatomic molecules of diverse bond character. 19 It was shown that only charge uxes from QTAIM are consistent with simple physical arguments based on, for instance, dissociation of polar covalent bonds into neutral fragments and the existence of a harpoon mechanism in highly ionic diatomic molecules.…”
Section: Introductionmentioning
confidence: 99%